Mineral Composition of Pistachio (Pistacia vera L.) from Siirt, Turkey - KAZANKAYA, AHMET; BALTA, FIKRI; OZTURK, NESLIHAN; SONMEZ, FERIT (Asian Journal of Chemistry, 2010)
This study evaluates fruit-leaf nutrient contents and some pomological characteristics of pistachio selections from Siirt, south-eastern Turkey. Based on average values of two years, pistachio selections had 1.21-1.93 g fruit weight, 0.46-0.81 g kernel weight and 31.5-49.0 % kernel percentage. Their splittings were high, medium and low. Harvest time was between 20 September and 05 October. Fruits of selections contained 3.04-4.20 % N, 0.168-0.441 % P, 0.348-1.084 % K, 0.189-2.819 % Ca, 0.762-2.445 % Mg, 11,14-330.36 ppm Fe, 2.36-4.82 ppm Mn, 4.23-31.49 ppm Zn and 0.43-22.71 ppm Cu. Their leaf nutrient contents were 1.12-2.18 % N, 0.006-0.132 % P, 0.44-2.47 % K, 2.82-6.35 % Ca, 2.97-4.67 % Mg, 25.3-314.8 ppm Fe, 6-67 ppm Mn, 11.0-33.2 ppm Zn and 4.75-91.79 ppm Cu. Findings of selections were compared with those of 'Siirt' Turkish pistachio cultivar.